2011
DOI: 10.1016/j.jash.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal blood pressure pattern and development of prehypertension or hypertension in young adults: the CARDIA study

Abstract: Nondippers (people whose sleep systolic blood pressure (SBP) fails to decrease >10% from daytime SBP) have increased risk of cardiovascular disease. The prevalence of nondipping in younger adults has not been well-studied, nor has its value for predicting hypertension. We examined the prevalence of nondipping in a sub-study of the Coronary Artery Risk Development in Young Adults (CARDIA) Study. We used Cox regression to estimate the hazard ratio (HR) conferred by nondipping for incident prehypertension or hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…In addition, a longitudinal analysis from the Coronary Artery Risk Development in Young Adults (CARDIA) study demonstrated that blunted nocturnal blood pressure dipping in adolescents is associated with an increased risk of hypertension later in life (48). Given that the present study evaluated healthy young adults, our findings may be more informative for future risk of hypertension.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, a longitudinal analysis from the Coronary Artery Risk Development in Young Adults (CARDIA) study demonstrated that blunted nocturnal blood pressure dipping in adolescents is associated with an increased risk of hypertension later in life (48). Given that the present study evaluated healthy young adults, our findings may be more informative for future risk of hypertension.…”
Section: Discussionmentioning
confidence: 78%
“…The primary finding of this study is that low sleep efficiency is significantly correlated to blunted SAP dipping, which is a known risk factor for future hypertension in young adults (48). In addition, low sleep efficiency was also associated with higher nocturnal heart rate and blunted heart rate dipping, which are clinically relevant indices of cardiovascular prognostic value that are often overlooked in this area of research (36).…”
Section: Perspectives and Significancementioning
confidence: 75%
See 1 more Smart Citation
“…Based on our results, it is possible that these early BP aberrations cause myocardial damage, leading to elevated hs-cTNT, before clinically overt hypertension is recognized. Compatible with this hypothesis, it has been shown elsewhere that "non-dippers" (an abnormal diurnal BP pattern where sleep systolic BP fails to decrease >10% from daytime systolic BP and a known riskfactor for subsequent hypertension 6 ), are more likely to have prevalent detectable troponin levels by hs-cTNT assays 34 .…”
Section: Discussionmentioning
confidence: 99%
“…4 The onset of hypertension is an insidious process that typically occurs over many years and is often preceded by altered diurnal BP patterns and prehypertension. 5,6 While hypertension is diagnosed using defined BP thresholds, risks associated with elevated BP occur on a continuous spectrum. Indeed, even early, pre-hypertensive, BP abnormalities can induce structural heart changes 7 , potentially affording the opportunity both to detect persons at risk for overt hypertension and to initiate timely preventive strategies.…”
Section: Introductionmentioning
confidence: 99%